EKSTRAK BUAH Morinda citrifolia L. SEBAGAI BAHAN BIOAKTIF DALAM GEL TABIR SURYA: FORMULASI DAN ANALISIS NILAI SPF - Dewi Dianasari; Nuri; Siti Muslichah; Endah Puspitasari; Anisatul Himmah; Cempaka Maryami Rakasiwi (Alma Ata University Press, 2026)
Background: Exposure to ultraviolet (UV) radiation can cause skin damage. To mitigate this, sun protection is needed. Noni fruit (Morinda citrifolia L.) has the potential to protect the skin due to secondary metabolites, namely phenolics and flavonoids. Both possess antioxidant and UV-absorbing properties, contributing to the extract's photoprotective activity and sunscreen potential. Objective: This study aims to determine the optimal formula for sunscreen gel preparations using noni fruit extract, as well as the antioxidant capacity and SPF. Methods: The optimization used a 22-factorial design, with the tested response parameters including organoleptic properties, homogeneity, pH, spreadability, adhesiveness, and viscosity. Results: Based on the research conducted, the optimal formula for the gel preparation is Carbopol at 1,959% and propylene glycol at 10,515%. The noni fruit extract gel at a concentration of 10% has an antioxidant capacity with an IC50 of 941,6100 ± 27,8651 μg/mL and an SPF of 21,1702 ± 0,7166. Conclusion: Noni fruit extract gel at a concentration of 10% has limited antioxidant activity but has a moderate SPF value for UV protection.